2020
DOI: 10.1111/trf.15667
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor as a thrombotic and inflammatory mediator in critical illness

Abstract: The endothelial exocytosis of high‐molecular‐weight multimeric von Willebrand factor (vWF) may occur in critical illness states, including trauma and sepsis, leading to the sustained elevation and altered composition of plasma vWF. These critical illnesses involve the common process of sympathoadrenal activation and loss of the endothelial glycocalyx. As a prothrombotic and proinflammatory molecule that interacts with the endothelium, the alterations exhibited by vWF in critical illness have been implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 97 publications
(212 reference statements)
2
15
0
Order By: Relevance
“…However, most patients with TIC have preserved platelet counts and evidence of circulating populations of activated platelets, yet paradoxically impaired ex vivo aggregation responses 117,118 . This phenomenon is described as 'platelet exhaustion' , due to injury and shock 119 and is driven by endothelial release of TF, platelet activating factor and vWF 99,120 that activates platelets beyond what is needed for primary haemostasis at the local sites of injury, thereby creating a pool of activated circulating platelets that are 'spent' or exhausted following the release of their procoagulant and anticoagulant factors. These circulating exhausted platelets cannot contribute to primary haemostasis or ex vivo aggregation assays that require platelets to respond to stimulation 112,119 .…”
Section: Platelet Dysfunctionmentioning
confidence: 99%
“…However, most patients with TIC have preserved platelet counts and evidence of circulating populations of activated platelets, yet paradoxically impaired ex vivo aggregation responses 117,118 . This phenomenon is described as 'platelet exhaustion' , due to injury and shock 119 and is driven by endothelial release of TF, platelet activating factor and vWF 99,120 that activates platelets beyond what is needed for primary haemostasis at the local sites of injury, thereby creating a pool of activated circulating platelets that are 'spent' or exhausted following the release of their procoagulant and anticoagulant factors. These circulating exhausted platelets cannot contribute to primary haemostasis or ex vivo aggregation assays that require platelets to respond to stimulation 112,119 .…”
Section: Platelet Dysfunctionmentioning
confidence: 99%
“… 9 , 10 A recent study analyzed markers of endothelial cell activation or damage in patients with COVID-19, including soluble P-selectin, soluble thrombomodulin, and VWF, and identified endotheliopathy as a common pathophysiology of COVID-19 disease, particularly as patients become critically ill. 6 Endothelial dysfunction and VWF release can occur in critically ill patients with acute respiratory distress syndrome in the absence of COVID-19. 11 However, our subset of stroke patients with elevated VWF and factor VIII did not suffer a critical illness resulting in intubation, acute respiratory distress syndrome, or sepsis. The majority of our patients had preexisting vascular risk factors, suggesting prior endothelial dysfunction, perhaps rendering them more susceptible to developing an endotheliopathy and thrombosis in the setting of COVID-19.…”
Section: Discussionmentioning
confidence: 84%
“…vWF is produced and secreted by endothelial cells following disturbance or damage ( Lip and Blann, 1997 ). It has been implicated in the development of coagulopathies and systemic inflammatory response ( Plautz et al, 2020 ), and was found increased in severe Covid-19 patients ( Escher et al, 2020 ). IL-6, a pro-inflammatory cytokine, was found to contribute to Covid-19-related hyperinflammatory syndrome ( Hlh Across Speciality Collaboration UK et al, 2020 ) and to correlate with Covid-19 severity ( Han et al, 2020 ; Herold et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%